An assessment of mesoporous silica nanoparticle architectures as antigen carriers - Huang, X; Townley, HE (MDPI, 2020)
Mesoporous silica nanoparticles (MSNPs) have the potential to be used as antigen carriers due to their high surface areas and highly ordered pore network. We investigated the adsorption and desorption of diphtheria toxoid as a proof-of-concept. Two series of nanoparticles were prepared—(i) small pores (SP) (<10 nm) and (ii) large pores (LP) (>10 nm). SBA-15 was included as a comparison since this is commercially available and has been used in a large number of studies. External diameters of the particles ranged from 138 to 1509 nm, surface area from 632 to 1110 m2/g and pore size from 2.59 to 16.48 nm. Antigen loading was assessed at a number of different ratios of silica-to-antigen and at 4 °C, 20 °C and 37 °C. Our data showed that protein adsorption by the SP series was in general consistently lower than that shown by the large pore series. Unloading was then examined at 4 °C, 20 °C and 37 °C and a pH 1.2, 4.5, 6.8 and 7.4. There was a trend amongst the LP particles towards the smallest pores showing the lowest release of antigen. The stability of the MSNP: antigen complex was tested at two different storage temperatures, and storage in solution or after lyophilization. After 6 months there was negligible release from any of the particles under any of the storage conditions. The particles were also shown not to cause hemolysis.